Maritime Context in Learning at School: Systematic Literature Review - Susanti Susanti; Nainggolan Elsa Ernawati; Siregar Nur Asma Riani (BIO Web of Conferences, 2023)
The aim of this research is to determine the maritime context and the implementation of the integration of the maritime context in learning at school. The method used in this research is a qualitative method with a systematic literature review or literature study type method. The research results show that the maritime context is a situation that utilizes all the potential at sea, be it fisheries, maritime affairs, mining, tourism and transportation. Implementation of maritime context integration in learning at school is the process of implementing or carrying out an activity that integrates maritime insight, be it fisheries, maritime affairs, mining, tourism and transportation into the process of teaching and learning activities at school such as in material/content and learning media. By integrating the maritime context in learning activities, it can make it easier for students to understand learning concepts by observing and viewing learning in the surrounding environment.